Policy Analysis Of Pelagic Thresher Shark (Alopias Pelagicus) Conservation And The Role Of Local Communities In Preservation In Indonesian Waters - Soares, Yohanes; Bunyani, Nur Aini; Finmeta, Abdonia W. (Green Publisher Indonesia, 2025)
The thresher shark (Alopias pelagicus) is an apex predator that plays an important role in marine ecosystems, but its population continues to decline due to overexploitation and habitat degradation. This study analyzes the thresher shark conservation policy in the Alor Marine Conservation Area, East Nusa Tenggara (NTT), and the role of local communities in supporting the conservation of this species. Data were collected through in-depth interviews, participant observation, and document analysis, then analyzed using qualitative methods. The results show that the conservation policy in the Alor MPA faces challenges in implementation, such as low community participation and limited monitoring resources. This study recommends a community-based approach to improve the effectiveness of thresher shark conservation in a sustainable manner.